Nightbane - Aster, Alex (Aster, Alex. Lightlark saga, 2023)
"Isla Crown has secured the love of two powerful rulers and broken the curses that plagued the six realms for centuries, but few know the true origins of her powers. Now, in the wake of a crushing betrayal, Isla finds herself hungry for distraction, preferring to frequent Lightlark's seductive haunts instead of embracing her duties as the newly crowned leader of two separate realms. Worse, her fellow rulers haven't ceded victory quietly, and there are others in Isla's midst who don't believe her ascent to power was earned. As certain death races toward Lightlark and secrets from the past begin to unravel, Isla must weigh her responsibility to her people against the whims of the most dangerous traitor of all: her heart. Alex Aster's intricate world expands after the riveting culmination of the Centennial games, delving more deeply into Isla's memories of her past, as her future hurtles toward two possible fates" --